The engineering of human joint replacements - McGeough, J. A. (Joseph A.), 1940- (John Wiley & Sons Inc., 2013)
"Includes an anatomy of the human skeleton: bone, tissue ligament, muscle and cartilage, in order to provide the engineering student with the medical context required"--